Proportion of early treatment seeking for sexually transmitted infections and associated factors among patients attending youth friendly service in Bahir Dar City health centers, Northwest, Ethiopia - Getachew Zeleke; Alemtshay Mekonnen; Tigist Abuhay; Muluken Chanie Agimas (BMC, 2024)
Abstract Background Sexually transmitted infection is a common public health issue of youths and is characteristically transmitted through sexual intercourse. Even though early treatment for sexually transmitted infection is very important to reduce further complications and economic burden, studies to identify the proportion and the possible factor of early treatment seeking is rare in Ethiopia. Objective To assess the proportion of early treatment seeking for sexually transmitted infections and associated factors among patients attending youth friendly service in Bahir Dar city health centers, northwest, Ethiopia 2023. Method Institutional based Cross-sectional study was used among 407 participants from April 25 to May 24 /2023. A systematic random sampling technique was used to select the participants. An interview-administered questionnaire was used for data collection, whereas Epi-data version 4.6.0.2 and the statistical package for statistical science version 23 were used for data entry and analysis respectively. A frequency table and bar chart were used for descriptive analysis. Multiple binary logistic regression was employed to identify the factors at p-value of <0.05. The necessary assumption of the model was also checked by the Hosmer and Lemishow test. Results The response rate of this study was 391 (96.1%) and the proportion of early treatment for sexually transmitted infection was 108 (27.6%, 95%CI; 23-32). Good knowledge about sexually transmitted infection (AOR=1.98, 95CI%; 1.13-3.47) know about their HIV status (AOR=1.95, 95%CI; 1.13-3.36), perceive severity of sexually transmitted infection (AOR=11.23, 95%CI; 6.15-20.45), and not fear the stigma about being infected with sexually transmitted infection (AOR=2.29, 95%CI; 1.32-3.96) were the significantly associated factors for early treatment of sexually transmitted infection. Conclusion and recommendation The proportion of early treatment for sexually transmitted infection in Bahir Dar city was low. Knowledge about STIs, testing/ knowing HIV status, perception of the severity about sexually transmitted infection, and fear of stigma about sexually transmitted infection were the statistically significant factors for early treatment of sexually transmitted infection. So the government better give attention to health education and other health promotion activities to increase the knowledge of youths about sexually transmitted infection and to change their perception of sexually transmitted infection.